Art education in the Philippines - Parina, Gloria M.
This article discusses the status of the arts in the country and its implications for art education and the training of arts teachers. It is the responsibility of art educators to equip the future generation with the basic competence in absorbing the bounty of human endeavors and be able to assimilate them into their cultural system. The trend in curriculum designing in Philippine education is integration. The University of the Philippines Integrated School integrated arts and music education with communication arts in English following a humanities approach to the three disciplines involved.
Keywords: University of the Philippines (Diliman). Integrated School -- Curricula; Art -- Study and teaching -- Philippines; Art teachers -- Training of -- Philippines; Curriculum planning -- Philippines